Interconception Health Behaviors Among Women With a Prior Preterm Birth [16O]. (May 2017) - Batra, Priya; Scibetta, Emily; Celaya, Anna K.; Jackson, Ashaki; Greenwell, Lisa; Saleeby, Erin
Abstract : INTRODUCTION: Preterm birth (PTB) is a leading cause of infant morbidity and mortality; the strongest risk factor for PTB is a mother's history of preterm delivery. Certain modifiable risk factors for PTB could be addressed between pregnancies to decrease recurrence rates. This study describes associations between previous PTB and select associated interconception health behaviors. METHODS: Between December 2013 and August 2016, community health workers conducted intake interviews with pregnant women enrolling into the MAMA'S Los Angeles County prenatal care program. Select interconception health behaviors associated with PTB were assessed in women's current pregnancies, including: trimester of prenatal care initiation, pregnancy intent, and tobacco use at conception. Participants self-reported all outcomes and PTB history. Chi-square tests were performed. RESULTS: Analyses included data from 3, 259 women, 322 (9.9%) of whom reported a prior PTB. There was no significant association between prior PTB and early (first trimester) initiation of prenatal care in the current pregnancy (chi-square=.40, P=.53). Women reporting a prior PTB were not significantly more likely to report that their current pregnancy was intended (chi-square=.01, P=.92). The proportion of women reporting tobacco use at conception did not differ between women who did (9.7%) and did not (9.9%) report a prior PTB (chi-square=.02, P=.90). CONCLUSION: Women reporting a prior PTB did not differ significantly from women without a PTB history with respect to select self-reported interconception health behaviors. Findings suggest that women with a prior PTB could benefit from interventions that could reduce the risk of recurrence by addressing relevant interconception health behaviors.